DNA barcoding and phytochemical profiling of wild plant "Lal lat tan" from Imugan, Sta Fe, Nueva Vizcaya, Philippines - John Dave C. Aquino; Lariza Mae Pajarillaga; Jerwin R. Undan (International Journal of Secondary Metabolite, 2018)
The Philippines hosts a wide-ranging diversity of plant species with pharmacological potential. Species identification on the basis of DNA sequences has been done for some time in plants and used to detect variations among the sequences specifying genetic divergence as a result of molecular evolution during the course of time. In this study, molecular approach as well as phylogentic analysis were conducted to identify the wild plant "Lal lat tan" collected from Imugan, Sta Fe, Nueva Vizcaya. In addition, thin layer chromatography was conducted to determine the bioactive compounds present in the wild plant. For molecular approach, the genomic DNA was extracted from the young leaves using CTAB and amplified using the nrDNA ITS marker. The PCR amplified product was sequenced and subjected for search query analysis using BLAST and was identified as Dendrocnide meyeniana. Using chloroform+methanol as solvent system, the result revealed the presence of saponins, phenols, tannins, flavonoids, anthrones, anthraquinones, terpenes and steroids which are considered as active medicinal phytochemical constituents. Lal lat tan is a wild plant and was known for having stinger leaf that lead to severe itchiness and swelling of eyes and face when touched.